Ground-freezing experience on the east side access Northern Boulevard crossing, New York - Schmall, Paul; Dawson, Andrew (ICE Publishing, 2017)
A brief review is given of ground freezing technology as a means of providing groundwater cut-off and temporary structural support in weak ground for transportation tunnelling and shaft-sinking operations. Then detailed coverage of a particular case history is reported in variable soils in Queens, New York. As part of the upgrading of rail access from Long Island into Manhattan, a tunnel was required that necessitated a frozen arch structure under a ‘live’ roadway and rail lines. The installation, development and performance of the frozen zone are described. At two small locations groundwater continued to flow through the line of the frozen arch, the heat in the newly arrived groundwater being greater than the capacity of the ground freezing technique to remove that heat, thereby preventing final ‘closure’ by frozen soil at those points. The remedial works to overcome these difficulties are described. Some conclusions are drawn concerning the reasons when and why these localized unfrozen ‘windows’ can be anticipated in freeze zones and about the requirements for remedial solutions.